Bilaterality of temporal EEG findings in limbic encephalitis compared to other mesiotemporal epilepsies – A retrospective cohort study. (March 2022) - Langenbruch, Lisa; Spalke, Julia; Krähling, Hermann; Sundermann, Benedikt; Brix, Tobias; Meuth, Sven; Wiendl, Heinz; Kovac, Stjepana
Highlights: Bilateral temporal EEG changes are frequent in mesiotemporal epilepsies. Similar results comparing hippocampal sclerosis, tumors, and limbic encephalitis. Bilaterality was more frequent in immunotherapy naïve limbic encephalitis. Abstract: Background: The current diagnostic criteria for autoimmune limbic encephalitis (LE) stress bilaterality of temporal MRI and EEG findings. This retrospective cohort study aimed to determine whether bilaterality is indeed more common in LE than in other mesiotemporal epilepsies. Methods: We compared EEG findings mostly from long-term EEG monitoring in patients with LE (n=59), hippocampal sclerosis (HS, n=44), and mesiotemporal tumors (n=24). Results: Bilateral temporal EEG findings including temporal slowing, interictal epileptiform discharges (IED), and seizures were equally frequent with 37% in LE, 32% in HS, and 17% in tumor patients. Bilateral independent temporal seizures were infrequent with 3%, 9%, and 0%, respectively. Patients with seropositive LE more often showed an EEG without IED or seizure patterns than patients with seronegative LE (n=37) with a higher proportion of unilateral temporal findings. Patients with immunotherapy naïve LE (n=40) showed a higher proportion of bilateral temporal IED or slowing in comparison with tumor patients. Conclusions: We conclude that unilateral or absent temporal EEG findings are common in LE and should not discourage this differential diagnosis.